2010
DOI: 10.1016/j.neurobiolaging.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that γ-secretase mediates oxidative stress-induced β-secretase expression in Alzheimer's disease

Abstract: Abstractβ-secretase (BACE1), an enzyme responsible for the production of amyloid β-peptide (Aβ), is increased by oxidative stress and is elevated in the brains of patients with sporadic Alzheimer's disease (AD). Here we show that oxidative stress fails to induce BACE1 expression in presenilin-1 (γ-secretase)-deficient cells and in normal cells treated with γ-secretase inhibitors. Oxidative stress-induced β-secretase activity and sAPPβ levels were suppressed by γ-secretase inhibitors. Levels of γ-and β-secretas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 28 publications
3
64
0
Order By: Relevance
“…Second, our data revealed the existence of a positive feedback loop in which c-secretase activity results in up-regulation of BACE1 expression. Previously Minopoli et al (2007) had shown a correlation between the induction of OS and the increase of c-secretase cleavage on APP and then Jo et al (2010) confirmed the finding that c-secretase up-regulates BACE1 expression.…”
Section: Ab Production Is a Major Link Between Oxidative Stress And Pmentioning
confidence: 73%
“…Second, our data revealed the existence of a positive feedback loop in which c-secretase activity results in up-regulation of BACE1 expression. Previously Minopoli et al (2007) had shown a correlation between the induction of OS and the increase of c-secretase cleavage on APP and then Jo et al (2010) confirmed the finding that c-secretase up-regulates BACE1 expression.…”
Section: Ab Production Is a Major Link Between Oxidative Stress And Pmentioning
confidence: 73%
“…Inferior parietal lobule and cerebellum specimens from the brains of 5 patients with AD and 5 control subjects that had been enrolled in the University of Kentucky Alzheimer's Disease Center Autopsy Program were used for this study. All patients with AD met both clinical diagnostic criteria and neuropathological diagnostic criteria of AD (41,42). The control subjects had no history or neuropathological signs of a brain disorder.…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative stress-induced BACE1 expression is regulated by γ-secretase activity, providing evidence of a feed-forward pathogenic mechanism of AD in which oxidative stress increases Aβ production, which then enhances oxidative stress (29). Molecular identification of the γ-secretase complex has shown that four different members are essential for this enzymatic activity: presenilin 1 (PS1), anterior pharynx-defective (APH-1), presenilin enhancer 2 (PEN-2), and nicastrin (NCT) (27,28).…”
Section: Figmentioning
confidence: 99%